Pandemic crisis management : threats and opportunities for humans and planet Earth - Osmanagić-Bedenik, Nidžara (Array, 2020)
The first recorded COVID-19 case emerged in China and, within a few months, it has spread to 210 countries globally, thrusting people into danger, uncertainty, fear, and of course physical and social isolation. The impacts of this pandemic are significant for every aspect of our lives. Crises include risk and chances at the same time. As Shakespeare said, “There is nothing either good or bad, but thinking makes it so“. This paper focuses on threats and opportunities of the pandemic crisis for humans and planet Earth. Crisis is defined as an unplanned and unwanted process of limited duration and impact, which endangers primary goals, and produces ambivalent outcome. Crisis management encompasses three phases: avoiding the crisis, identifying its symptoms when they occur and finding ways out of the crisis. There are several research questions related to that. First, could the COVID-19 crisis be avoided? Or at least could its onset be recognized early? Second, how can the pandemic crisis be measured in terms of its intensity and depth? Third, which ways lead us out of the crisis? And fourth, which lessons have to be learned? Exploring the novel literature and research findings provides new insights into the pandemic crisis and the crisis management process, which is the aim of the paper. With its results and major conclusions this paper provides a holistic perspective to the pandemic crisis and crisis management.